📅  最后修改于: 2023-12-03 15:28:09.075000             🧑  作者: Mango
我们来证明一下:
左边:(cos θ sec θ)cot θ
= cos θ * (1/cos θ) * (cos θ/sin θ)
= cos θ * cos θ / (sin θ * cos θ)
= cos² θ / sin θ
= 1 - sin² θ / sin θ
= (1 - sin θ)(1 + sin θ) / sin θ
= cos θ / sin θ (因为1 - sin θ = cos² θ)
右边:tan θ
= sin θ / cos θ
= 1 / (cos θ / sin θ)
= 1 / cot θ
把右边的式子带到左边去,得到:
左边 = cos θ / sin θ = 右边
所以,(cos θ sec θ)cot θ = tan θ。证毕。
# 证明 (cos θ sec θ)cot θ = tan θ
我们来证明一下:
左边:(cos θ sec θ)cot θ
= cos θ * (1/cos θ) * (cos θ/sin θ)
= cos θ * cos θ / (sin θ * cos θ)
= cos² θ / sin θ
= 1 - sin² θ / sin θ
= (1 - sin θ)(1 + sin θ) / sin θ
= cos θ / sin θ (因为1 - sin θ = cos² θ)
右边:tan θ
= sin θ / cos θ
= 1 / (cos θ / sin θ)
= 1 / cot θ
把右边的式子带到左边去,得到:
左边 = cos θ / sin θ = 右边
所以,(cos θ sec θ)cot θ = tan θ。证毕。